POLA PERSEBARAN INDUSTRI DI KORIDOR JALAN RAYA BOGOR - Tambunan, Mangapul P. (UI Scholars Hub, 2002)
Spatial dispersed pattern of Industry at Jalan Raya Bogor Corridor. The corridor Jalan Raya Bogor, includes DKI Jakarta and West Java provinces have 186 industry, which different spatial dispersed pattern. The Industry has an impact to local community for worker industry. The analysis with nearness neighborhood and overlay map are conclusion as industry has cluster pattern at Cisalak Pasar, Cilangkap, and Cisalak district. And the industry patterns have random spatial at Tugu, Mekarsari, Sukamaju Baru, and Jatijajar district. The industry spatial has a dispersed pattern/uniform at Susukan, Ciracas, Pekayon, Curug, and Sukamaju district. The local community for worker industry has 62.04% senior high school and 2.81% elementary school or not education